Is the use of bipolar hemiarthroplasty over monopolar hemiarthroplasty justified? A propensity score- weighted analysis of a multicentre randomized controlled trial. (2023) - Gauthier, M. Comeau-; Bzovsky, S.; Axelrod, D.; Poolman, R. W.; Frihagen, F.; Bhandari, M.; Schemitsch, E.; Sprague, S.
No abstract available